Drivers of HIV self-test kit among Tanzanian men aged 15–49: findings from the 2022 TDHS-MIS cross-sectional study - Mbwiga Sote Aloni (AIDS Research and Therapy)
Abstract Introduction The introduction of the HIV self-test kit in the early 2000s was a major breakthrough in combating HIV. This study determines the social demographic and sexual behaviour driving the use of HIV self-test kits. Method The study used secondary data obtained from Tanzania DHS-MIS 2022. The survey uses a stratified two-stage sample design. The first stage involved the selection of clusters consisting of enumeration areas, and in the second stage of sampling, 26 households were selected from each cluster. Results The mean age = 28.6 years. Usage of HIV self-test kits was found to be low (3.9%). The odds of using HIV self-test kits were 2.2 and 6.6 times more likely among those with primary (aOR = 2.2, 95%CI = 2.2–2.3) and secondary (aOR = 6.6, 95%CI 6.6–6.7) education compared to those without education respectively. As age increases, the odds of using HIV self-test kits increases. Men residing in rural areas were about 40% less likely to use HIV self-test kits compared to those dwelling in urban areas (aOR = 0.6, P < 0.0001). Conclusion Significant demographic and sexual behaviour factors associated with the usage of HIV self-test kits include sex of household head, education level, marital status, wealth status, age, ever heard of sexually transmitted infection and condom use during sexual intercourse. HIV self-test kits were used more in urban areas than in rural areas. It is essential to raise awareness and improve access to HIV self-test kits for less informed populations, such as those living in rural areas.